2010
DOI: 10.1016/j.bbr.2010.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Choice between reinforcer delays versus choice between reinforcer magnitudes: Differential Fos expression in the orbital prefrontal cortex and nucleus accumbens core

Abstract: Lesions of the orbital prefrontal cortex (OPFC) and the nucleus accumbens core (AcbC) can disrupt performance in inter-temporal choice tasks, possibly by increasing the organism's sensitivity to delay and/or magnitude of reinforcement. This experiment examined whether exposure to an inter-temporal choice would induce neuronal activation in these areas, as indicated by enhanced expression of the Fos protein. Twelve rats were trained to press levers A and B under an adjusting-delay schedule in which a response o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 37 publications
(48 reference statements)
1
33
1
Order By: Relevance
“…The mPFC has been implicated in the representation of reward incentive value (Peters & Büchel, 2010;Peters & Büchel, 2011), the encoding of the magnitude of future rewards (Daw, O'Doherty, Dayan, Seymour, & Dolan, 2005), the determination of positive reinforcement values (Frank & Claus, 2006), the processing of immediate rewards (McClure, Laibson, Loewenstein, & Cohen, 2004), and the determination of cost and/or benefit information (Basten, Heekeren, & Fiebach, 2010;Cohen, McClure, & Yu, 2007). The orbitofrontal cortex (OFC) contributes to both impulsive and risky choice (da Costa Araújo et al, 2010;Mobini et al, 2002) and is a candidate for encoding the action value of a choice (Hare, O'Doherty, Camerer, Schultz, & Rangel, 2008;Kable & Glimcher, 2009;Kringlebach & Rolls, 2004;Peters & Büchel, 2010;Peters & Büchel, 2011;Schoenbaum, Roesch, Stalnaker, & Takahashi, 2009). While these structures form only a portion of the reward valuation system, they are likely to play a central role in the determination of domain-general valuation of rewards that guides impulsive and risky choice behavior and should drive the correlations.…”
Section: Domain-general Brain Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mPFC has been implicated in the representation of reward incentive value (Peters & Büchel, 2010;Peters & Büchel, 2011), the encoding of the magnitude of future rewards (Daw, O'Doherty, Dayan, Seymour, & Dolan, 2005), the determination of positive reinforcement values (Frank & Claus, 2006), the processing of immediate rewards (McClure, Laibson, Loewenstein, & Cohen, 2004), and the determination of cost and/or benefit information (Basten, Heekeren, & Fiebach, 2010;Cohen, McClure, & Yu, 2007). The orbitofrontal cortex (OFC) contributes to both impulsive and risky choice (da Costa Araújo et al, 2010;Mobini et al, 2002) and is a candidate for encoding the action value of a choice (Hare, O'Doherty, Camerer, Schultz, & Rangel, 2008;Kable & Glimcher, 2009;Kringlebach & Rolls, 2004;Peters & Büchel, 2010;Peters & Büchel, 2011;Schoenbaum, Roesch, Stalnaker, & Takahashi, 2009). While these structures form only a portion of the reward valuation system, they are likely to play a central role in the determination of domain-general valuation of rewards that guides impulsive and risky choice behavior and should drive the correlations.…”
Section: Domain-general Brain Mechanismsmentioning
confidence: 99%
“…The orbitofrontal cortex (OFC) contributes to both impulsive and risky choice (da Costa Araújo et al, 2010;Mobini et al, 2002) and is a candidate for encoding the action value of a choice (Hare, O'Doherty, Camerer, Schultz, & Rangel, 2008;Kable & Glimcher, 2009;Kringlebach & Rolls, 2004;Peters & Büchel, 2010;Peters & Büchel, 2011;Schoenbaum, Roesch, Stalnaker, & Takahashi, 2009). While these structures form only a portion of the reward valuation system, they are likely to play a central role in the determination of domain-general valuation of rewards that guides impulsive and risky choice behavior and should drive the correlations.…”
Section: Domain-general Brain Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal dependent variable, the adjusting delay to the larger reinforcer (d B ), is seen to oscillate during an extended period of training, the amplitude of oscillation gradually declining as d B approaches a quasi-stable value, which is usually taken to represent the indifference delay, d B(50) (Mazur 1987(Mazur , 1988. da Costa Araújo et al (2009Araújo et al ( , 2010 suggested that the pattern of oscillation of d B , analysed using Fourier transform, may provide information about the effects of neurobiological interventions on the organism's adaptation to changing delays to reinforcement. Evidence obtained to date indicates that the power spectrum of oscillations is sensitive to the ratio of reinforcer sizes (q B /q A ; da Costa Araújo et al 2009Araújo et al , 2010Valencia-Torres et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…da Costa Araújo et al (2009Araújo et al ( , 2010 suggested that the pattern of oscillation of d B , analysed using Fourier transform, may provide information about the effects of neurobiological interventions on the organism's adaptation to changing delays to reinforcement. Evidence obtained to date indicates that the power spectrum of oscillations is sensitive to the ratio of reinforcer sizes (q B /q A ; da Costa Araújo et al 2009Araújo et al , 2010Valencia-Torres et al 2011). However, it seems not to be affected by lesions of the AcbC (da Costa Araújo et al 2009Araújo et al , 2010.…”
Section: Introductionmentioning
confidence: 99%